A comparative evaluation of efficacy of Punica granatum and chlorhexidine on plaque and gingivitis - Sakshi Ahuja; Vidya Dodwad; Bhavna Jha Kukreja; Praful Mehra; Pankaj Kukreja (Wolters Kluwer Medknow Publications, 2011)
Background: Periodontal diseases are chronic bacterial infections that lead to gingival inflammation, periodontal tissue destruction, and alveolar bone loss. Acting as powerful allies in the fight against periodontal disease, natural compounds can help safeguard against lethal age-related diseases that emanate from our mouths. Punica granatum (pomegranate) shrub belongs to the Punicaceae family which has been used as an astringent, hemostatic, antidiabetic, antihelmintic, and also for diarrhea and dysentery. The aim of the present work was to investigate the possible efficacy of hydroalcoholic extract from Punica granatum fruit as an antiplaque and antigingivitis agent when compared with chlorhexidine. Materials and Methods: Twenty subjects diagnosed with chronic generalized gingivitis were selected and randomly divided into two groups: Group 1 - Pomegranate mouthwash and Group 2 - Chlorhexidine mouthwash. Punica granatum mouthwash was prepared using raw Punica granatum fruit. Patients were instructed to use the prescribed mouthwash for 15 days. Clinical evaluation was undertaken using the gingival index, the plaque index, and bleeding on probing at baseline, 7 days, and 15 days. Results: The clinical study observed significant improvement in gingival status in both the sites (P<0.05). Subjects using Punica granatum mouthwash showed significant improvement in bleeding and gingivitis score as compared with chlorhexidine. In contrast, Punica granatum was shown not to be so effective in reducing plaque scores. Chlorhexidine still remains as a standard in the reduction of plaque in subjects with gingivitis. Conclusion: Punica granatum mouthwash is beneficial in improving gingival status due to its profound styptic action, with sufficient reduction in plaque scores.